Role of vasoactive intestinal polypeptide in the internal anal sphincter relaxation of the opossum. - Nurko, S (1988)
The nature of the inhibitory neurotransmitter responsible for internal anal sphincter (IAS) relaxation in response to rectoanal reflex is not known. The objective of the present investigation was to examine the role of VIP in IAS relaxation in response to the rectoanal reflex in intact opossums with the use of VIP antagonists, [4CI-D-Phe6,Leu17] VIP and (N-AC-Tyr1,D-Phe2)-GRF (1-29)-NH2. Intraluminal pressures from the sphincter were monitored using low-compliance, continuously perfused catheters. VIP and the antagonists were administered close-intraarterially. The responses to VIP, rectoanal reflex, sacral nerve stimulation, and local intramural stimulation were examined before and after the VIP antagonists. The present studies in intact animals show: (a) VIP causes a dose-dependent fall in the IAS pressures by a direct action at the IAS smooth muscle; (b) VIP antagonists selectively and significantly antagonized the inhibitory action of VIP; and (c) VIP antagonists caused significant antagonism of the IAS relaxation caused by rectoanal reflex and the other neural stimuli. The antagonism of the IAS relaxation by the VIP antagonists, depending upon the volume of rectal distension used, ranged from 40% to 62% (P less than 0.05). From these results, we conclude that VIP acts as an inhibitory neurotransmitter for IAS relaxation during the rectoanal reflex.